The Influence of Physical Work Environment, Non-Physical Work Environment and Workload on Employee Job Satisfaction at PT. United Rope Medan - Tianggur Angelia Pardosi; Ainun Mardhiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of the physical work environment, non-physical work environment and workload on the job satisfaction of PT United Rope Medan employees. The research method used is a quantitative method. The sample in the study was 76 respondents. The data collection technique uses a questionnaire. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the physical work environment, non-physical work environment and workload have a significant and positive effect, both partially and simultaneously, on employee job satisfaction. Through the adjusted R Square value, it is known that the physical work environment, non-physical work environment and workload contribute 52.4% to employee job satisfaction and the remaining 47.6% is influenced by other variables.